Genotypic differences in concentration and bioavailability of kerneliron in tropical maize varieties grown under field conditions - Oikeh, S.O.; Menkir, A.; Maziya-Dixon, B.B.; Welch, R.; Glahn, Raymond P. (Informa UK Limited, 2003)
Iron deficiency is estimated to affect over one-half the world population. Improving the nutritional quality of staple food crops through breeding for high bioavailable iron represents a sustainable and cost effective approach to alleviating iron malnutrition. Forty-nine late maturing tropical elite maize varieties were grown in a lattice design with two replications in